2001
DOI: 10.1071/wf01036
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing fuels in the 21st Century

Abstract: This paper was presented at the conference ‘Integrating spatial technologies and ecological principles for a new age in fire management’, Boise, Idaho, USA, June 1999 The ongoing development of sophisticated fire behavior and effects models has demonstrated the need for a comprehensive system of fuel classification that more accurately captures the structural complexity and geographic diversity of fuelbeds. The Fire and Environmental Research Applications Team (FERA) of the USDA Forest Service, Pacific Northwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(85 citation statements)
references
References 4 publications
0
78
0
7
Order By: Relevance
“…Field measurements of FC were conducted in most fire-prone regions in the world, including the "arc of deforestation" in Amazonia, the boreal regions of North America, and savannas and woodlands in Africa, South America and Australia. Due to ecological, technical, and logistical reasons (e.g., wildfire versus prescribed fire), the FL and FC sampling procedures at these measurement locations have ranged in scope from simple and rapid visual assessment (e.g., Maxwell, 1976;Sandberg et al, 2001) to highly detailed measurements of complex fuel beds along lines (line transect method: van Wagner, 1968) or in fixed areas (planar intersect method; Brown, 1971) that take considerable time and effort. Most of the studies we found in the literature rely on the planar intersect method (PIM), where fuel measurement plots are typically divided into multiple, randomized smaller subplots.…”
Section: Measurementsmentioning
confidence: 99%
“…Field measurements of FC were conducted in most fire-prone regions in the world, including the "arc of deforestation" in Amazonia, the boreal regions of North America, and savannas and woodlands in Africa, South America and Australia. Due to ecological, technical, and logistical reasons (e.g., wildfire versus prescribed fire), the FL and FC sampling procedures at these measurement locations have ranged in scope from simple and rapid visual assessment (e.g., Maxwell, 1976;Sandberg et al, 2001) to highly detailed measurements of complex fuel beds along lines (line transect method: van Wagner, 1968) or in fixed areas (planar intersect method; Brown, 1971) that take considerable time and effort. Most of the studies we found in the literature rely on the planar intersect method (PIM), where fuel measurement plots are typically divided into multiple, randomized smaller subplots.…”
Section: Measurementsmentioning
confidence: 99%
“…To date, the development of fuel quantification and mapping systems has predominantly focused on providing arguments for specific fire models rather than representing the fundamental properties of fuel important to fire behaviour [67,68]. This means that the information collected is highly regional and focused on the limited number of parameters and methods specific to local vegetation types (e.g., Eucalyptus forests [69] or grasslands [70]).…”
Section: Parameterising Fuelmentioning
confidence: 99%
“…This is because where one model is used operationally, the appropriate measurements for alternative models are rarely collected, necessitating unit conversion and approximation. The adoption of a more universal system would increase the applicability of fire models and research findings, foster collaboration and reduce research duplication by allowing findings to be generalised across regions [35,68,122].…”
Section: Parameterising Fuelmentioning
confidence: 99%
“…This fuel information can then be collated in order to create the BFC fuel characteristics database. Key to the success of this process is the indexation of data quality (e.g., [43]), from which redundancies and poor-quality data sources can be removed. The system is designed to expand and, as this process evolves, users will be able to identify the fuel knowledge gaps and prioritise the necessary inventory work to attain suitable quantitative fuel descriptions.…”
Section: Management Implicationsmentioning
confidence: 99%